Критерії оцінки стану ландшафтної ділянки “трав’яниста діброва” дендропарку “Олександрія” НАН України - Galkin, S.I.; Dragan, N.V.; Doiko, N.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
The site “grassy or” park “oak forest of dendropark Olexandria of the NAS of Ukraine is artificially created decorative landscape. Criterion “simplification of the structure of oak plantations – the growth of its degradation” is not suitable to evaluate the status and viability of such oak. Found that the phytosanitary condition, vitality spectrum, the magnitude of the current apostasy landscape area “oak gardening type “of arboretum Olexandria is closer to the areas of oaks “Forest” type than to anthropogenically degraded oak forests. “Oak forest park” is viable durable planting and does not require the measures to optimize its structure by introducing additional layers.